Modelling and Simulation of H2-H2o Bubbly Flow Through a Stack of Three Cells in a Pre-Pilot Filter Press Electrocoagulation Reactor - Sandoval, A; Sandoval, A (Elsevier B.V., 2021)
Computational fluid dynamics simulations were carried out to describe the hydrodynamic characteristics of a two-phase bubbly flow in a filter-press flow reactor stack of three cells, which is typically used in electrocoagulation (EC). The hydrogen evolution reaction (HER) took place at the cathode; dissolution of aluminium occurred at the anode. The fundamental transport equations of momentum and electrical potential were simultaneously solved to simulate the H2-H2O flow. Continuous (H2O) and dispersed phase (H2) velocity fields were modelled via the Euler-Eulerian approach, using the biphasic Reynolds Averaged Navier-Stokes (RANS) equations and the standard k − ε turbulence model. The influence of volumetric flow rate (1.7 ≤ Q ≤ 15 cm3 s−1) and applied current density (–28 ≤ j ≤ –5 mA cm−2) was systematically addressed to calculate the fraction of dispersed phase and current distribution along the electrodes. The evolved H2 bubbles were transported away from the electrode by the liquid flow. The dispersion of H2 through the electrode gap showed a modest bubble curtain profile due to the liquid flow rate. A homogeneous current distribution along the electrode length was experienced due to the geometrical design of the electrochemical cell and the low degree of H2 dispersion. The velocity profiles of the H2-H2O mixture were different in each cell due to the change of flow direction. H2 bubbles increased the velocity of the liquid phase but the gas fraction of such bubbles resulted in a higher pressure drop. Good agreement between theoretical and experimental residence time distribution curves was achieved; the experimental aluminium dose released by the anode agreed well with the simulations. © 2020 Elsevier B.V.